2B.02: SERUM URIC ACID LEVEL, BUT NOT RENAL FUNCTION OR ARTERIAL STIFFNESS, IS ASSOCIATED TO WORSE BLOOD PRESSURE CONTROL IN GENERAL PRACTICE. (June 2015) - Cicero, A.; Rosticci, M.; Tartagni, E.; Parini, A.; Grandi, E.; D'Addato, S.; Borghi, C.; Group, Bhs
Abstract : Objective: Serum uric acid (SUA) has been associated to incident hypertension and increased risk of cardiovascular diseases. Our aims were to compare the haemodynamic characteristics of normotensives, undiagnosed hypertensives, controlled and uncontrolled hypertensive subjects, and to evaluate if SUA level could also been associated to a different control of blood pressure in pharmacologically treated patients. Design and method: During the last population survey of the Brisighella Heart Study we identified 146 new cases of arterial hypertension and 394 treated but uncontrolled hypertensive patients. Thus we compared their haemodynamic characteristics with those of age- (58 ± 14 years old) and sex-matched normotensive (N. 324) and controlled hypertensive (N. 470) subjects. Then, by logistic regression analysis, we evaluated which factors were associated to a worse blood pressure control under pharmacological treatment. Results: Pulse Wave Velocity (PWV) was significantly higher (p < 0.001) in undiagnosed hypertensive (9, 8 ± 2, 4 m/s) and pharmacologically uncontrolled hypertensive (10, 3 ± 4, 3 m/s) subjects, while controlled hypertensive subjects (8, 4 ± 2, 1 m/s) had PWV similar to the one of normotensive subjects (8, 2 ± 1, 9 m/s). A similar result has been observed for augmentation index (AI). SUA level was similar in normotensives and controlled hypertensives (5, 1 ± 1, 3 mg/dL and 5, 1 ± 1, 2 mg/dL, respectively), while significantly higher in untreated hypertensive and uncontrolled hypertensive patients (5, 4 ± 1, 3 mg/dL and 5, 4 ± 1, 4 mg/dL, respectively). The worse BP control was not associated to age or BMI nor to the estimated glomerular filtration rate, but to SUA (OR 1, 377, 95%CI 1, 184–1, 600), AI (OR 1, 066, 95%CI 1, 041–1, 092) e PWV (OR 1, 301, 95%CI 1, 189–1, 423). Conclusions: PWV and AI are similarly increased in newly diagnosed hypertensive patients and patients treated but not controlled, whereas PWV is similar in normotensive and well-treated subjects. The main predictors of worse BP control were SUA, AI and PWV.